Running-Related Injury From an Engineering, Medical and Sport Science Perspective - Papagiannaki, Maria; Samoladas, Efthimios; Maropoulos, Stergios; Arabatzi, Fotini (Frontiers in Bioengineering and Biotechnology, 2020)
Etiologic factors associated to running injuries are reviewed, with an emphasis on the transient shock waves experienced during foot strike. In these terms, impact mechanics are analyzed from both, a biomechanical and medical standpoint and evaluated with respect injury etiology, precursors and morbidity. The complex interaction of runner specific characteristics on the employed footwear system are examined, providing insight into footwear selection that could act as a preventive measure against non-acute trauma incidence. In conclusion, and despite the vast literature on running-related injury-risks, only few records could be identified to consider the effect of shoe cushioning and anthropometric data on injury prevalence. Based on this literature, we would stress the importance of such considerations in future studies aspiring to provide insight into running related injury etiology and prevention.